Total and individual carotenoid profiles in Solanum phureja of cultivated potatoes. 1: Concentrations and relationships as determined by spectrophotometry and HPLC - Burgos, G.; Salas, E.; Amoros, W.; Auqui, M.; Munoa, L.P.; Kimura, M.; Bonierbale, Merideth W. (Elsevier, 2009)
Total and individual carotenoid concentrations were determined by spectrophotometry and HPLC, in raw tubers of a sample of 23 accessions of Solanum phureja potatoes taken at random from the world germplasm collection following its stratification on tuber flesh color. Lutein, zeaxanthin, violaxanthin, antheraxanthin and ß-carotene were detected in all accessions and three distinct patterns of carotenoid accumulation were evidenced by cluster analysis. Accessions in group 1 showed the highest concentrations of total carotenoids (1258–1840 µg 100 g-1 FW) comprised largely of zeaxanthin (658–1290 µg 100 g-1 FW) with very low or no presence of ß-carotene (below 5.4 µg 100 g-1 FW). Accessions in group 2 presented moderate total carotenoid concentrations with violaxanthin, antheraxanthin, lutein and zeaxanthin as the major carotenoids. Accessions in group 3 showed low concentrations of total carotenoids (97–262 µg 100 g-1 FW) and very low or no zeaxanthin, with lutein and violaxanthin as the predominant carotenoids and relatively high concentrations of ß-carotene (up to 27 µg 100 g-1 FW). Five accessions with significant concentrations of zeaxanthin were identified with the accession 703566 showing the highest concentration (1290 µg 100 g-1 FW). This value is to our knowledge higher than any value previously reported for potatoes, including those achieved through genetic modification. For the 23 S. phureja accessions, total carotenoid concentration was positively and significantly correlated with antheraxanthin and zeaxanthin concentrations, and negatively and significantly correlated with ß-carotene concentration.